The association between kidney function-standardized serum uric acid levels and stroke risk: insights from the National Health and Nutrition Examination Survey - Deng, Xinmin; Kuang, Kunlin; Zhong, Yumei; Lai, Rui; Lv, Xiaofeng; Liu, Shanshan; Liu, Meijun; Liang, Jingtao; Yang, Dongdong (Frontiers in Aging Neuroscience, 2025)
BackgroundPrevious studies on the relationship between serum uric acid to serum creatinine ratio (SUA/SCr) and stroke have shown inconsistent results. This study investigates the association between SUA/SCr and stroke risk using data from the National Health and Nutrition Examination Survey (NHANES).Materials and methodsA cross-sectional analysis was conducted using NHANES data from 1999 to 2018. Weighted univariate and multivariate logistic regression models were used to evaluate the association between SUA/SCr and stroke. The restricted cubic spline (RCS) curve was used to explore the nonlinear relationship between SUA/SCr and stroke risk.ResultsIn the regression model adjusted for all covariates, the OR (95% CI) for the association between SUA/SCr and stroke was 0.84 (0.78, 0.92), indicating a significant association between SUA/SCr and stroke risk. When SUA/SCr was analyzed as a categorical variable by quartiles, participants in the highest SUA/SCr quartile (Q4) had a 53% lower risk of stroke compared to those in the lowest quartile (Q1), with an OR (95% CI) of 0.47 (0.31, 0.71). RCS analysis revealed a nonlinear relationship between SUA/SCr and stroke risk (nonlinearity p = 0.048). Before the nonlinear inflection point (6.33), stroke risk significantly decreased as SUA/SCr increased. After this point, the decrease in stroke risk with increasing SUA/SCr slowed down markedly.ConclusionOur study indicates that higher SUA/SCr levels are associated with a lower risk of stroke. However, further prospective longitudinal studies are required to establish the causal relationship and explore the potential role of SUA/SCr in stroke risk assessment and prevention strategies.